Prevalence of malaria and treatment procurement in three local government areas of Ekiti State, Nigeria - Adewole, Segun; Odeyemi, Dolapo; Omotosho, Olaitan (International Journal of Scientific World, 2017)
Malaria remains a major health problem in Nigeria. It accounts for over 60% outpatient visit and 30% hospital admission in Nigeria. Ineffective treatment of malaria is also one of the factors responsible for its prevalence. The prevalence of malaria and treatment procurement was studied in Ekiti state, Nigeria. The study was carried out using well-structured questionnaire comprising of three sections A to C, Socio-economic, input and output data; data on method, cost of treatment of malaria and expenditure were obtained. Multistage random sampling technique was adopted. The result obtained showed that males with percentage prevalence of 53% were more infected than females with 47%. Respondent with symptoms of fever and chills was 48.2% while 51.8% complained of headache and pains. 80.3%% of the respondents have knowledge of malaria transmission while 19.7% have no idea. 46.7% of respondents spent less than 1000 naira for treatment procurement while 53.3% spent more than 1000naira. However, there was a significant difference (p<0.05) between males and female's susceptibility to malaria disease. Therefore, as at the time of study, there is prevalence of malaria in the communities despite the knowledge of the respondents on transmission of malaria and treatment procured.